“Control biológico del gusano barrenador del tallo de maíz (Diatraea saccharalis) empleando Trichogramma pretiosum”. - Páliz Méndez, Erik Vicente (2020)
The stem borer (Diatraea saccharalis) is one of the main pests that attack corn, and it can lead to significant losses in both yield and economics. Considering the above, the present investigation aimed to evaluate the effect of the biological control of the corn stem screwworm (D. saccharalis) using Trichogramma pretiosum. The investigation was carried out in the Fumisa area belonging to Buena Fe province of Los Ríos at the Hacienda “Santa Anita” at km 38 via Quevedo-Santo Domingo. Releases of T. pretiosum were made in the crop, and its parasitic effect was evaluated in the strata: low (T1), medium (T2) and high (T3) of the plantation. The results obtained allowed us to identify that there is a greater oviposition of D. saccharalis eggs in T1: low stratum of the corn crop, with an average of 26 eggs per week, while in T3: high stratum there is significantly less number of oviposited eggs, with 15 eggs for every 10 plants. The percentages of parasitism decrease as the evaluation height of D. saccharalis eggs increases, in such a way that in T1: low stratum there was 65.93% parasitism, while, in T2: middle stratum and T3: high stratum, these values decreased to 56.17 and 47.47% parasitism. The biocontroller proved to be more efficient for the control of eggs in T1: low stratum, parasitizing 65.93% of the total eggs collected in the 7 weeks of evaluation, being 38.89% more efficient than in T3: high stratum, showing a capacity of parasitize 58.30% of the total eggs evidenced in the study. Keywords: Biocontroller, Biological control, Zea mays L.